Juridical Analysis of Non-Consensual AI-Generated Sexual Content as Digital Voyeurism in Indonesian Criminal Law - Devy Fitri Syahrani; Muhammad Athaya Primananda; Nirwasita Zada Paramesti; Yearta Kurnia Zalifah; Andriyanto Adhi Nugroho (Penerbit Yayasan Daarul Huda Kruengmane, 2026)
This study examines Non-Consensual AI-Generated Sexual Content as a form of digital voyeurism under Indonesian criminal law. Using a normative juridical method, the research analyzes the application of the Electronic Information and Transactions Law, Pornography Law, Sexual Violence Law, and Personal Data Protection Law in addressing deepfake pornography that manipulates a victim’s image without consent. The findings show that such acts constitute layered criminal offenses, including electronic data manipulation, obscenity violations, electronic-based sexual violence, and personal data misuse. However, law enforcement faces significant challenges, including technical detection issues, lack of AI-specific regulations, perpetrator anonymity, and cross-border jurisdiction barriers. This study highlights the need for dedicated AI regulation and strengthened law-enforcement capacity to ensure effective victim protection.